Contras and comandantes: armed movements and forest conservation in Nicaragua's Bosawas biosphere reserve - Kaimowitz, D.; Faune, A. (Food Products Press, 2003)
In the 1980s, Nicaragua's Sandinista government faced armed mestizo and indigenous insurgencies in much of the nation's central and eastern region. After the Sandinistas lost the 1990 elections, the in-coming government signed peace agreements with the insurgents and facilitated their return to civilian life. With the war over, the Nicaraguan army greatly reduced its troop strength, leaving tens of thousands of people unemployed. Within a few years, however, many former insurgents and soldiers took up arms again for multiple and complex reasons. This paper examines how three groups that rearmed influenced forest conservation in the buffer zone of Nicaragua's Bosawas biosphere reserve between 1991 and 1999. The three groups were the Mestizo Northerm Front 3-80 (FN 3-80) and the Andres Castro United Forces (FUAC), and the Miskito YATAMA movement. The presence of these armed groups impeded the government from taking coercive action to remove farmers from the reserve's nucleus. It also limited the advance of cattle ranching. At times, the groups favored logging, at times they did not. The armed conflicts have tended to keep out prudent foreign investors and encourage the presence of smaller companies willing to take greater risks.